Non-relational Embedding Verbs: Quotes and Reports - García Núñez, José María; Orrequia-Barea, Aroa (Complutense Journal of English Studies, 2020)
Some verbs cannot have their clausal complements replaced by referential expressions salva congruitate and/or veritate. This makes it difficult to analyse them as denoting relations of the type expressed by run-of-the-mill transitive verbs. The main goal in this work is to find an explanation for why some English embedding verbs are relational while others fail to be so. The question is, why can the latter, but not the former verbs have their embedded clauses replaced by direct speech complements? A comparison in the relevant contexts of the related categories of direct and indirect quotation reveals an important degree of coincidence that calls for (a) an overlapping semantic treatment, and (b) an interpretation of their often invoked differences as due to the contrasting semantic requirements of the class of verbs that fails to express a relation, non-relational ones. For us, the key distinguishing factor is utterance denotation, the differences between the two main classes of verbs identified in the work deriving from reliance on either the form or the content of the utterances involved. In order to account for these facts, we propose a substantial revision of the Davidsonian approach to clausal complementation.